Kajian Pengembangan Wisata Religi Di Kabupaten Banjar Kalimantan Selatan - Muhammad Arief Anwar (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2019)
One of South Kalimantan's development priorities is to realize South Kalimantan as one of the national tourism destinations. One type of tourism that is now developing is religious tourism. Banjar Regency, with its capital city of Martapura is well-known as